Efeito do tratamento por plasma na proliferação de fibroblastos e esterilização de membranas de quitosana - Macêdo, Marina de Oliveira Cardoso (2013)
Chitosan is being studied for use as dressing due their biological properties. Aiming to expand the use in biomedical applications, chitosan membranes were modified by plasma using the following gases: nitrogen (N2), methane (CH4), argon (Ar), oxygen (O2) and hydrogen (H2). The samples were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), contact angle, surface energy and water absorption test. Biological Tests were also performed, such as: test sterilization and proliferation of fibroblasts (3T3 line). Through SEM we observed morphological changes occurring during the plasma treatment, the formation of micro and nano-sized valleys. MFA was used to analyze different roughness parameters (Ra, Rp, Rz) and surface topography. It was found that the treated samples had an increase in surface roughness and sharp peaks. Methane plasma treatment decreased the hydrophilicity of the membranes and also the rate of water absorption, while the other treatments turned the membranes hydrophilic. The sterilization was effective in all treatment times with the following gases: Ar, N2 and H2. With respect to proliferation, all treatments showed an improvement in cell proliferation increased in a range 150% to 250% compared to untreated membrane. The highlights were the treatments with Ar 60 min, O2 60 min, CH4 15 min. Observing the results of the analyzes performed in this study, it appears that there is no single parameter that influences cell proliferation, but rather a set of ideal conditions that favor cell proliferation